2017
DOI: 10.3390/nano7110394
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Corrosion and Biological Properties of Room-Temperature Sputtered Aluminum Nitride Films with Dissimilar Nanostructure

Abstract: Aluminum Nitride (AlN) has been long time being regarded as highly interesting material for developing sensing applications (including biosensors and implantable sensors). AlN, due to its appealing electronic properties, is envisaged lately to serve as a multi-functional biosensing platform. Although generally exploited for its intrinsic piezoelectricity, its surface morphology and mechanical performance (elastic modulus, hardness, wear, scratch and tensile resistance to delamination, adherence to the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 98 publications
2
18
0
Order By: Relevance
“…The observed hardness behavior is closely related to the processes of film growth and the resulting film microstructure, which yielded variation in the film hardness values. Nevertheless, all H values were within 22-30 GPa range, superior to the ones registered in the case of films obtained by other deposition techniques [22,[42][43][44][45][46][47]. In general, a higher deposition temperature enhances the reaction at the surface of the substrate and promotes the formation of crystallites in the growing film [48].…”
Section: Nanoindentation Testingmentioning
confidence: 56%
“…The observed hardness behavior is closely related to the processes of film growth and the resulting film microstructure, which yielded variation in the film hardness values. Nevertheless, all H values were within 22-30 GPa range, superior to the ones registered in the case of films obtained by other deposition techniques [22,[42][43][44][45][46][47]. In general, a higher deposition temperature enhances the reaction at the surface of the substrate and promotes the formation of crystallites in the growing film [48].…”
Section: Nanoindentation Testingmentioning
confidence: 56%
“…Finally, we mention in Section 3 that AlN is a unique material in a sense that it has a high mechanical, thermal and chemical stability. Therefore, we will discuss a few works [ 87 , 88 , 89 , 90 ] in Section 5.11 that sputtered and characterized their AlN thin films for applications in difficult environments. This information will be helpful for the new research that would like to employ this material to make sensors/devices at those conditions.…”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pamentioning
confidence: 99%
“…In order to crystallize the initially amorphous as-deposited Bio-HA films, without inducing a strong oxidation of the Ti6Al4V implant substrate, a post-deposition thermal-treatment was applied at 500 • C/1 h in air. Since the RF-MS technology produces smooth layers [33,62] and the SEM method does not have enough contrast to distinguish the fine topological details, the morphology of Bio-HA films deposited onto mirror-polished substrates could be better revealed by atomic force microscopy (AFM) analysis. An NTEGRA Probe NanoLaboratory System (NT-MDT, Moscow, Russian Federation) equipped with an NSG01 cantilever with 10 nm tip was used.…”
Section: Deposition Of Bio-ha Thin Films By Rf-msmentioning
confidence: 99%
“…The increased intensity of the 002 peak of Bio-HA film with respect to the ICDD file indicated that the Bio-HA crystallites elicited a preferred orientation along the c-axis, normal to the substrate. The c-axis texturing is characteristic to sputtered films synthesized from materials of the hexagonal system [34,36,60,62,67]. The average crystallite size determined based on the full width at the half-maximum (FWHM) of (002) planes reflections was estimated by applying the Scherrer equation [68].…”
Section: Functionalization Of the Cranial Mesh With A Bioceramic Layermentioning
confidence: 99%